Appropriate Complementary Feeding and Parenting Practices to Prevent Stunting in Children - Sofia, Norlaila; Prihatanti, Nur Rohmah; Aprilea, Noor Adha; Nashriyah, Asy-syifa (Interest : Jurnal Ilmu Kesehatan, 2025)
Background: Stunting is a major public health problem caused by chronic malnutrition and recurrent infections, especially during the First 1000 Days of Life. Banjar Regency recorded the highest stunting prevalence in South Kalimantan, reaching 44.4% in 2022. Parenting practices such as early initiation of breastfeeding (IMD), exclusive breastfeeding, appropriate complementary feeding (MP-ASI), vitamin A supplementation, and handwashing with soap (CTPS) play an essential role in stunting prevention. This study aimed to analyze the association between parenting practices and stunting incidence in Banjar Regency.  Methods: An observational study with a cross-sectional design was conducted among mothers with children aged 12–24 months. Samples were selected using multistage random sampling. Data were collected through anthropometric measurements and structured questionnaires assessing parenting practices. Data were analyzed using the chi-square test with a significance level of p<0.05 and odds ratio (OR) estimation. Results: Most mothers practiced IMD (90%), provided MP-ASI (80%), and administered vitamin A supplementation (80%), but more than half did not exclusively breastfeed (43.3%). The prevalence of stunting was 40%. Statistical analysis showed a significant association between MP-ASI practices and stunting incidence (p-value = 0.026; OR = 0.082). However, IMD, exclusive breastfeeding, vitamin A supplementation, and CTPS were not significantly associated with stunting.  Conclusion: Complementary feeding practices have a strong protective effect against stunting. Therefore, strengthening maternal knowledge and community-based education on optimal complementary feeding practices should be prioritized in stunting prevention strategies.